The Probability of the May 2024 Geomagnetic Superstorm - S. Elvidge; D. R. Themens (Space Weather)
Abstract In May 2024, a series of coronal mass ejections resulted in the first “severe” (G4‐level) geomagnetic storm watch in nearly 20 years. This event evolved into a significant space weather event, including an “extreme” (G5) geomagnetic storm, moderate (S2) solar radiation storm, and strong (R3) radio blackout. The widespread visibility of auroras at unusually low latitudes attracted global media attention. Using extreme value theory (EVT), this study estimates the return periods for the May 2024 storm based on several geomagnetic indices. The results indicate that while the storm's magnitude was a 1‐in‐12.5‐year event, its duration was a 1‐in‐41‐year event. This discrepancy highlights the storm's unusual longevity compared to its intensity. Updated EVT analyses incorporating recent data refine these return period estimates, providing critical insights into the frequency of such extreme space weather events.